Mathematical procedure for prediction of dental anxiety in children with inherited bleeding disorders - Vujkov, Sanja; Cvetićanin, Livija; Bajkin, Branislav; Blagojević, Duška; Milekić, Bojana; Vučinić, Predrag (Vojnosanitetski pregled, 2022)
Background/Aim. The dental anxiety in children is commonly measured applying the Dental Anxiety Scale (DAS) and the level is statistically treated. However, there are no studies on prediction of development of dental anxiety. The aim of this study was to develop a mathematical procedure for dental anxiety prediction based on the statistical values. Methods. Mathematical relation between the dental anxiety and aging was developed using the interpolation method based on the statistical values. It was supposed that the anxiety level is a polynomial function of the age. The obtained function was tested on the healthy children and those with inherited bleeding disorders. By mathematical fitting procedure using statistical data, the analytical relation for prediction of dental anxiety as a function of aging was developed. Results. According to prediction function, it was found that for healthy population the dental anxiety has the tendency to increase quite slowly or to remain almost constant after the age of 18. In the patients with inherited bleeding disorders, the DAS score would increase even after age of 18. The treatment of the anxiety in children with inherited bleeding disorders is optimal at about the age of 12 when they become aware of their illness. Conclusion. The introduced prediction function gives the tendency of DAS score development which enables timely adequate action in reducing dental anxiety. The predicted DAS score may be used as a control measure of oral health.
Keywords: blood coagulation disorders, inherited; forecasting; child; dental anxiety; models, theoretical